The Influence of Training Methods and Arm Muscle Strength Towards Volleyball Smash at Youth and Sports Department of Kendal (Dissporsa) (Journal of Physical Education and Sports, 2022)
The background of the research is to know the difference between the hanging ball training method and the rubber band at the Dissporsa volleyball club. The aims of this study were: 1) to analyze the effect of the hanging ball and rubber rope method on volleyball smashes and 2) to analyze the effect of high and low arm muscle strength on volleyball smashes. 3) To find out the interaction between training methods and arm muscle strength on volleyball smash hits. This research method was a factorial design experiment of 2 x 2. The factorial design involved two factors as independent variables, namely the exercise method and arm muscle strength. The population of the study was 24 people who were members at Dissporsa Kendal volleyball club. Data analysis used a two-way ANAVA hypothesis test. The results of the research obtained by the Ball Group hung by 16,583 points of smash results better than the rubber rope group which was 7,750 points of smash results. The high arm muscle strength group of 15,250 points of smash results was better than the low arm muscle strength group of 9,083 smash points. The conclusion of the hanging ball training method has a much better smash. High arm muscle strength has a much better smash result. There is an interaction between the hanging ball method and arm muscle strength on smash results and there is an interaction between rubber rope training and arm muscle strength against smash hits at the Dissporsa Kendal volleyball club.